Population Structure of the Juvenile Penaeid Shrimps Occurring in the Sandspit Backwaters of Karachi Coast, Pakistan (Biological Sciences - PJSIR, 2006)
Ten species of juvenile penaeid shrimps were collected from Sandspit backwaters, Karachi coast, Pakistan. The genus Penaeus was represented by P. penicillatus, P. merguiensis, P. indicus, P. monodon, P. semisulcatus and P. japonicus, the genus Metapenaeus was represented by M. monoceros, M. stebbingi and M. affinis, whereas the genus Parapenaeopsis was represented by a single species, P. stylifera. Population structure, such as the species composition, seasonal abundance, size distribution, sex ratios, and the length frequency distribution were studied for seven species. The remaining three species (Penaeus semisulcatus, P. japonicus and Parapenaeopsis stylifera) were found only once and thus excluded from the above noted studies. The juvenile population in the Sandspit backwaters was dominated by M. monoceros (40.97%) and P. penicillatus (32.64%), which altogether constituted 73.6% of the population. These were followed in the order of abundance by M. stebbingi (10.73%) and P. merguiensis (9.29 %). The three less abundant species were P. indicus (3.27 %),affinis (2.14%) and P. monodon (0.87 %). P. penicillatus dominated during July to October, M. monoceros dominated during March to June, and M. stebbingi dominated during December and January. The average total length of P. penicillatus (juveniles) was found to be 57.1 mm with a range from 11 mm to 119 mm. In P. merguiensis, the total length varied from 11 mm to 123 mm with the average length of 54.3 mm. The total length of P. indicus varied from 12 to117 mm, with the average length of 60 mm. The total length of P. monodon (juveniles) ranged from 49 to 163 mm, and the average length was 105 mm. The total length of M. monoceros ranged from 11 to 93 mm, with the average size of 46 mm. The size of M. stebbingi (juveniles) varied from 10 to 90 mm in its total length and the average size was found to be 31 mm. In M. affinis, the total length varied from 18 to 95 mm, with the average length of 55 mm. The overall sex ratios in juveniles of all the species were not found to be significantly different. However, in certain size classes, the sex ratios deviated significantly.